Foreign Portfolio Investment-Economic Growth Nexus in Nigeria: Co Integration and Granger Causality Analyses (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The study employed Wald causality methodology to uncover the direction of causal relationship between foreign portfolio investment and economic growth in Nigeria between 1986 and 2013. The empirical results suggest that foreign portfolio investment and economic growths are positively cointegrated indicating a stable long run equilibrium relationship. Further, the findings revealed bidirectional causality between foreign portfolio investment and economic growth and the complementary role of domestic savings and interest rate in growth.